Patients with calcific aortic stenosis exhibit systemic molecular evidence of ischemia, enhanced coagulation, oxidative stress and impaired cholesterol transport. (15th December 2016) - Mourino-Alvarez, Laura; Baldan-Martin, Montserrat; Gonzalez-Calero, Laura; Martinez-Laborde, Carlos; Sastre-Oliva, Tamara; Moreno-Luna, Rafael; Lopez-Almodovar, Luis F.; Sanchez, Pedro L.; Fernandez-Aviles, Francisco; Vivanco, Fernando; Padial, Luis R.; Akerstrom, Finn; et al.
Abstract: Background: The most common valve diseases are calcific aortic stenosis (AS) and aortic regurgitation (AR). The former is characterized by thickening of valve leaflets followed by progressive calcification, which produces progressive aortic valve (AV) narrowing, increased pressure afterload on the left ventricle (LV) and subsequent LV hypertrophy. On the other hand, AR is due to malcoaptation of the valve leaflets with resultant diastolic reflux of blood from aorta back to the LV producing volume and pressure overload and progressive LV dilatation. In order to isolate the molecular mechanisms taking place during AS, we have used an integrated "–omic" approach to compare plasma samples from AS and from AR patients used as controls. The final purpose of this work is to find molecular changes in response to the calcification of the AV, diminishing the effects of the AV dysfunction. Methods and results: Using two-dimensional difference gel electrophoresis (2D-DIGE) and gas chromatography coupled to mass spectrometry (GC-MS) in a cohort of 6 subjects, we have found differences in 24 protein spots and 19 metabolites, respectively. Among them, 7 proteins and 3 metabolites have been verificated by orthogonal techniques (SRM or turbidimetry): fibrinogen beta and gamma chain, vitronectin, apolipoprotein C-II, antithrombin III, haptoglobin, succinic acid, pyroglutamic acid and alanine. Classification according to their main function showed alterations related to coagulation, inflammation, oxidative stress, response to ischemia and lipid metabolism, defining 4 different molecular panels that characterize AS with high specificity and sensitivity. Conclusion: These results may facilitate management of these patients by making faster diagnostics of the disease and better understand these pathways for regulating its progression. Graphical abstract: Figure 1 Scheme of the workflow of this study. A combined proteomics and metabolomics approach was performed for the discovery phase. Verification of these results was carried out using SRM and turbidimetry to describe a molecular panel of AS. Highlights: A pro-coagulation and pro-inflammatory state exists in aortic stenosis patients. Stenotic patients show impairment in lipid metabolism and response to ischemia. Four sensitive and specific molecular panels for aortic stenosis have been defined.